Improving Students Activity and Students Learning Outcomes by Using Collaboration of Mind Mapping and Picture and Picture Models - Mahmudi Mahmudi; Fury Styo Siskawati (Universitas Islam Jember, 2018)
The purpose of the research is to describe the students activities in using mix of mind mapping and picture and picture model. To describe the students learning outcomes in using mix of mind mapping and picture and picture model model. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VII at MTs Kaliwining Jember. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: mind mapping, picture and picture, students activity, and students learning outcomes